Evaluating appropriate red blood cell transfusions: a quality audit at 10 Ontario hospitals to determine the optimal measure for assessing appropriateness. Issue 10 (27th July 2016) - Spradbrow, Jordan; Cohen, Robert; Lin, Yulia; Armali, Chantal; Collins, Allison; Cserti‐Gazdewich, Christine; Lieberman, Lani; Pavenski, Katerina; Pendergrast, Jacob; Webert, Kathryn; Callum, Jeannie
Abstract : BACKGROUND: Evaluating the appropriateness of red blood cell (RBC) transfusion requires labor‐intensive medical chart audits and expert adjudication. We sought to determine the appropriateness of RBC transfusions at 10 hospitals using retrospective chart review and to determine whether simple metrics (proportion of single‐unit transfusions, RBCs/100 acute inpatient days, proportion of transfusions with pretransfusion hemoglobin <80 g/L or posttransfusion hemoglobin <90 g/L) could be used as surrogate markers of appropriateness by comparing their values with the results from the audit. STUDY DESIGN AND METHODS: An initial block of 30 RBC units was dually adjudicated for appropriateness followed by additional blocks of 10 units until the difference between the cumulative percentage of appropriate RBC units in the preceding block and final block was <3%. Pearson correlation tests were used to evaluate associations between the metrics and percentages of appropriate transfusions per hospital. Two‐by‐two tables were used to assess the utility of the metrics to classify transfusions for appropriateness. RESULTS: Of the 498 units audited, 78% were adjudicated as appropriate (κ = 0.9603), with significant variability between institutions (p < 0.0001). Fifty audits or less were required at nine of the institutions. The values of the metrics were not found to have significant correlations with appropriateness, and the metric that misclassified the smallest proportion of transfusions for appropriateness was pretransfusion hemoglobin <80 g/L, at 24%. CONCLUSIONS: Our findings suggest that a chart audit of 50 RBC transfusions with adjudication using robust criteria is the optimal means of evaluating RBC transfusion appropriateness at an institution for benchmarking and quality‐improvement initiatives.